Intermittent hypoxia-induced enhancement of sociability and working memory associates with CNTNAP2 upregulation - Zhang, Qing; Xu, Lu; Bai, Yang; Chen, Peiye; Xing, Mengen; Cai, Fang; Wu, Yili; Song, Weihong (Frontiers in Molecular Neuroscience, 2023)
Introduction Hypoxia is an environmental risk factor for many disorders throughout life. Perinatal hypoxia contributes to autism spectrum disorder (ASD), while hypoxic conditions in the elderly facilitate memory deficits. However, the effects of hypoxia on adolescence remains elusive. CNTNAP2 is a critical molecule in ASD pathogenesis with undefined mechanisms. We investigate hypoxia’s impact on adolescence and the underlying mechanism related to CNTNAP2. Methods Three-chamber social approach test, Y maze, Morris Water Maze and Open Field Test were applied to evaluate behavioral alterations. Immunoblotting, 5′- RACE and dual-luciferase reporter assay were performed to examine CNTNAP2 protein expression, transcription start site (TSS) of human CNTNAP2 gene and CNTNAP2 promoter activity, respectively. Results Intermittent hypoxia treatment improved social behaviors and working memory in adolescent mice. CNTNAP2 was increased in the brains of hypoxia-treated mice. The sequencing results identified the TSS at 518 bp upstream of the translation start site ATG. Hypoxia upregulated CNTNAP2 by interacting with functional hypoxia response elements in CNTNAP2 promoter. Conclusion Intermittent hypoxia enhanced sociability and working memory associated with CNTNAP2 upregulation. Our study provides novel insights into intermittent hypoxia’s impact on development and the interaction between genetic and environmental risk factors in ASD pathogenesis.